STUDI EROS. DAN CIR' H.DROLIKA ALiRAN DIPt:RMUKAAN LAHAN (Erosion Study and Hydroulic Row on Land Surface) - MT., Ir. Siswanto; Anwar, Nadjadji (MAPETA, 2002)
The purposed of the study is to identify of characteristics hydraulic flow and erosion as real picture on incipient motion-m sediment transport. The study is conducted in types of soil namely Alfisol and Entisol. They have a wide range utilization and a high erosion susceptibility. Simulation has been conducted by dropping eight different rain height to undisturbed soil block samples with 2.500 square em, width and 10 em thickness and with 9 % and 17 % land slopes. The results shows that surface run off not play in detachment of soil particle if equal with rain pellet and dispersion of water, but its transport sediment. Surface run off on plot standard in two kind of soil (Alfisol and Entisol) is laminar sub critics with Reynold number 140,2 and 136,2; Froude Number 0,940 and 0,980; drag force 9,02 and 4,44 Nm-2. Whereas 17% slope is super critics with Reynolrd Number 206,2 and 78,1; Froude number 1,219 and 1,286 and drag force 14,79 and 9,76 Nm-2.· Key Words: Erosion, hydraulic characteristic, sediment transport